2017
DOI: 10.3171/2016.8.spine151371
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative urinary retention in patients undergoing elective spinal surgery

Abstract: OBJECTIVE Postoperative urinary retention (POUR) is a common problem leading to morbidity and an increased hospital stay. There are limited data regarding its baseline incidence in patients undergoing spinal surgery and the risk factors with which it may be associated. The purpose of this study was to evaluate the incidence of POUR in elective spine surgery patients and determine the factors associated with its occurrence. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
7
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 27 publications
4
87
7
2
Order By: Relevance
“…The rate of occurrence of POUR among female patients in this study was 2.9%. This is similar to the rate reported in many previous studies, even though the incidence of POUR for other types of operations has been reported as being lower among female than male patients . Generally, it is known that administering an alpha‐blocker reduces the risk of POUR .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The rate of occurrence of POUR among female patients in this study was 2.9%. This is similar to the rate reported in many previous studies, even though the incidence of POUR for other types of operations has been reported as being lower among female than male patients . Generally, it is known that administering an alpha‐blocker reduces the risk of POUR .…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Huang et al suggested that age is a significant risk factor for POUR in their study of 314 patients who underwent TKA (HR 1.33, P < 0.001). In univariate analyses of 397 patients and 205 patients who underwent spinal surgery, Altschul et al and Lee et al found significant differences in age between the POUR and non‐POUR groups ( P = 0.002 for the study of Altschul et al and P = 0.001 for the study of Lee et al). However, neither study found such a significant relationship when retrospective multivariate analysis was used .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations